SUSTAINABLE INDUSTRY IN PERU: CHALLENGE FOR NATIONAL DEVELOPMENT - Romero B., Alfonso (2002)
The present document, propose five factors by sustainable development, within Peruvian Industry and it's implement sustainable respect like global activities between endogen and exogen variables what regard the modern enterprise to be competitive into the world where the information is a strategic tools by industrial leader.